A comparison of growth patterns between non‐indigenous Halophila nipponica and the native sympatric Zostera marina on the southern coast of the Korean peninsula. (25th September 2017) - Park, Jung‐Im; Kim, Jeong Bae; Lee, Kun‐Seop
Abstract: The growth dynamics of two co‐occurring seagrass species, Zostera marina and Halophila nipponica, were examined on the southern coast of the Korean peninsula. Zostera marina is a native dominant seagrass species in Korean coastal waters, whereas H . nipponica is a non‐native tropical and subtropical species that has extended its distributional range to the temperate coastal areas of Korea. To examine the differences in the growth dynamics of H . nipponica and Z . marina, their morphology, density, productivity and biomass, as well as local environmental conditions, were monitored monthly from January 2008 to July 2009. Underwater irradiance at the study site was the highest in April 2009 and the lowest in January 2008. Water temperature ranged from 10.4°C in January 2009 to 24.8°C in September 2008. Significant differences in growth dynamics were observed between the species, due to the effect of water temperature at the study site. Density and areal productivity were the highest in April 2008 and June 2008, respectively, for Z . marina but the highest in July 2008 for H . nipponica . Leaf size, shoot height and shoot weight were the highest in July 2008 for Z . marina but the highest in August 2008 or September 2008 for H . nipponica . The productivity of both species was strongly correlated with water temperature at the study site. However, the productivity of these species was not strongly correlated with underwater irradiance or the nutrient availability of either the water column or sediment pore water. Zostera marina exhibited the ecological characteristics of a temperate seagrass, whereas H . nipponica retained the features of a subtropical/tropical seagrass, even after adapting to the temperate coastal waters of Korea.